Consensus organizing : a community development workbook : a comprehensive guide to designing, implementing, and evaluating community change initiatives /: a community development workbook : a comprehensive guide to designing, implementing, and evaluating community change initiatives. ([2009]) - Ohmer, Mary L; DeMasi, Karen
No abstract available